Construction of DNA Hemicatenanes from Two Small Circular DNA Molecules - Gaillard, Claire; Strauss, François (PLOS ONE, 2015)
DNA hemicatenanes, one of the simplest possible junctions between two double stranded DNA molecules, have frequently been mentioned in the literature for their possible function in DNA replication, recombination, repair, and organization in chromosomes. They have been little studied experimentally, however, due to the lack of an appropriate method for their preparation. Here we have designed a method to build hemicatenanes from two small circular DNA molecules. The method involves, first, the assembly of two linear single strands and their circularization to form a catenane of two single stranded circles, and, second, the addition and base-pairing of the two single stranded circles complementary to the first ones, followed by their annealing using DNA topoisomerase I. The product was purified by gel electrophoresis and characterized. The arrangement of strands was as expected for a hemicatenane and clearly distinct from a full catenane. In addition, each circle was unwound by an average of half a double helical turn, also in excellent agreement with the structure of a hemicatenane. It was also observed that hemicatenanes are quickly destabilized by a single cut on either of the two strands passing inside the junction, strongly suggesting that DNA strands are able to slide easily inside the hemicatenane. This method should make it possible to study the biochemical properties of hemicatenanes and to test some of the hypotheses that have been proposed about their function, including a possible role for this structure in the organization of complex genomes in loops and chromosomal domains.